Association of virginiamycin and multiple supplement for cattle fed a high-quality tropical forage - Vidal, Raphaela C.; Lima, Nicole S.A.; Sampaio, Claudia B.; Duarte, Marcio S.; Detmann, Edenio (Frontiers in Animal Science, 2022)
The aim of this study was to evaluate the effect of adding virginiamycin to either mineral mixture or multiple supplement on intake, digestion, ruminal fermentation profile, rumen microbial production, blood metabolites, and liver metabolism of zebu heifers fed high-quality tropical forage. Eight Brahman heifers were assigned to a duplicate 4 × 4 Latin Square design. The treatments were: mineral mixture, mineral mixture with virginiamycin, multiple supplement, and multiple supplement with virginiamycin. The mineral mixture was provided daily at 120 g/animal. The multiple supplement was formulated to provide 300 g of crude protein (CP)/kg as fed, contained mineral mixture, corn grain, and urea: ammonium sulfate, and was daily provided at 200 g/animal. The amount of supplemental virginiamycin was based on a maximum theoretical response on animal performance (50 mg/100 kg body weight) and daily mixed to the supplements types. The treatments were compared according to a 2 × 2 factorial arrangement (mineral mixture and multiple supplement, with or without virginiamycin). The virginiamycin supplementation di not alter voluntary either voluntary intake or digestibility. Using the multiple supplement decreased forage and digested organic matter (DOM) intake, but increased dietary CP:DOM ratio. The multiple supplement increased the ruminal ammonia concentration and the acetate-to-propionate ratio. Virginiamycin increased urinary nitrogen (N) when provided along with multiple supplement. Fecal N was decreased by multiple supplement. Despite of these effects, treatment did not alter either body N accretion or microbial N production in the rumen. Virginiamycin decreased the blood IgF-1. The gene hepatic gene expression for propionyl-CoA carboxylase was increased by virginiamycin. Virginiamycin increased the hepatic gene expression of both citrate synthase and pyrivate carboxylase when mineral mixture was provided, but decreased it when animals were fed multiple supplement. Using a low-intake multiple supplement with a high CP content for cattle fed high-quality forage causes a substitutive effect on forage intake, but keeps nitrogen accretion unchanged. That pattern indicates an improvement in feed efficiency. On the other hand, virginiamycin supplementation seems to cause some post-prandial influences, which may vary according to the type of supplement. Those influences apparently improve animal efficiency.